Anesthesia And Recovery: Comparing Methods To Minimize Drug Effects On Emergence Time (The Review of Diabetic Studies, 2025)
This synthesis examines the comparative effects of total intravenous anesthesia (TIVA) and inhalational anesthesia on emergence time, recovery quality, and postoperative cognitive function, with a focus on adult and elderly surgical populations. TIVA, primarily utilizing propofol and short-acting opioids, offers precise plasma concentration control and rapid offset, potentially reducing residual sedation and neuroinflammatory responses. Inhalational agents such as sevoflurane and desflurane provide adjustable depth via inspired gas concentrations, with emergence profiles influenced by blood-gas solubility and patient physiology. Pharmacokinetic and pharmacodynamic differences, alongside adjunctive medications, contribute to variability in awakening speed and recovery metrics. Elderly patients exhibit altered drug metabolism and distribution, affecting anesthetic clearance and cognitive outcomes. Objective recovery measures, including time to eye opening, extubation readiness, and post-anesthesia care unit discharge criteria, reveal nuanced distinctions between modalities, with TIVA often associated with reduced postoperative nausea and vomiting. Cognitive assessments yield mixed results, reflecting heterogeneity in surgical types, baseline function, and testing intervals. Ethical considerations emphasize informed consent processes sensitive to perioperative stress and cognitive capacity, while balancing patient safety with research rigor requires adaptive protocols and vigilant monitoring. This integrated evaluation suggests that anesthetic choice should consider individual patient factors, surgical context, and recovery goals to optimize perioperative outcomes.